Pawedness Trait Test (PaTRaT)—A New Paradigm to Evaluate Paw Preference and Dexterity in Rats - Cunha, Ana M.; Esteves, Madalena; das Neves, Sofia P.; Borges, Sónia; Guimarães, Marco R.; Sousa, Nuno; Almeida, Armando; Leite-Almeida, Hugo (Frontiers in Behavioral Neuroscience, 2017)
In rodents, dexterity is commonly analyzed in preference paradigms in which animals are given the chance to use either the left or the right front paws to manipulate food. However, paw preference and dexterity at population and individual levels are controversial as results are incongruent across paradigms. We have therefore developed a semi-quantitative method - the pawdeness trait test (PaTRaT) - to evaluate paw preference degree in rats. The PaTRaT consists in a classification system, ranging from +4 to -4 where increasingly positive and negative values reflect the bias for left or right paw use, respectively. Sprague-Dawley male rats were confined into a metal rectangular mesh cylinder, from which they can see, smell and reach sugared rewards with their paws. Due to its size, the reward could only cross the mesh if aligned with its diagonal, imposing additional coordination. Animals were allowed to retrieve 10 rewards per session in a total of 4 sessions while their behavior was recorded. PaTRaT was repeated 4 and 8 weeks after the first evaluation. To exclude potential bias, rats were also tested for paw fine movement and general locomotion in other behavioral paradigms as well as impulsivity (variable delay-to-signal), memory and cognitive flexibility (water maze). At the population level 54% of the animals presented a rightward bias. Individually, all animals presented marked side-preferences, >2 and <-2 for left- and right-sided bias, respectively, and this preference was stable across the 3 evaluations. Inter-rater consistency was very high between 2 experienced raters and substantial when 2 additional inexperienced raters were included. Left- and right-biased animals presented no differences in the ability to perform fine movements with any of the forelimbs (staircase) and general locomotor performance. Additionally, these groups performed similarly in executive function and memory tasks. In conclusion, PaTRaT is able to reliably classify rats’ pawedness direction and degree.